Hubungan Antara Faktor Usia dan Jenis Kelamin dengan Kejadian Kanker Kolorektal di Rumah Sakit Umum Cut Meutia Pada Tahun 2020 - Sri Rahayu , Mulyati; Sayuti, Muhammad; Raihan, Muhammad (FAKULTAS ILMU KESEHATAN UNIVERSITAS MUHAMMADIYAH PAREPARE, 2023)
Colorectal cancer is cancer that is in the colon or rectum. This research to determine the relationship between age and gender on the incidence of colorectal cancer at the Cut Meutia General Hospital in 2020. This type of research is an analytic observational approach with a cross sectional approach. This research uses a total sampling technique. The number of colorectal cancer patients with male sex is more than female with 18 male patients (60%) and 12 female patients (40%). The total number of cancer patients in 2020 is 290 patients, 265 of whom are cancer patients other than colorectal cancer where 71 patients were male patients (26.8%) and 194 female patients (73.2%). Colorectal cancer patients aged over 60 years were the highest number with 10 patients (33.3%), while cancer patients other than colorectal cancer patients aged 41-50 years were the highest number with 89 patients (33.6%). While the lowest number of colorectal cancer patients was at the age of 51-60 years with a total of 6 patients (20%) and the lowest number of cancer patients other than colorectal cancer patients aged over 60 years with a total of 50 patients (18.9%). with the incidence of colorectal cancer at the Cut Meutia General Hospital in 2020 with a p value of <0,001. There is no relationship between age and colorectal cancer at the Cut Meutia General Hospital in 2020 with a p value of 0,290. Colorectal cancer was found to be highest in male sex, and there is a relationship between gender and colorectal cancer but age was not associated with the incidence of colorectal cancer.